Mentalization-Based Treatment From the Patients’ Perspective – What Ingredients Do They Emphasize? - Morken, Katharina Teresa Enehaug; Binder, Per-Einar; Arefjord, Nina Margot; Karterud, Sigmund Wiggen (Frontiers in Psychology, 2019)
Objective: The aim of this study was to explore how patients with personality disorder (PD) and substance use disorder (SUD) experience mentalization based treatment (MBT), in particular what they consider useful and less useful elements of the therapy. Method: Semi-structured qualitative interviews with 13 participants were conducted. Participants were interviewed on their experience of the different elements of MBT, their experience of working in the transference and their view on MBT as a whole. Thematic analyses were performed within a hermeneutical-phenomenological epistemology, with emphasis on researcher reflexivity. Results: The following themes were found in the material: “I am not alone”, “Taking blinders off”, “Just say it”, “The paradox of trust”, and “Follow me closely”. Three of these themes concerned therapist interventions; these were interventions that involved addressing the relationship with the patients, addressing negative or unspoken feelings in the sessions and validating and tolerating patients’ affect. Two themes concerned group therapy experiences; these were the experience of sameness with co-patients in group and the experience of discovering different perspectives by co-patients in group. Conclusions: Patients experiences of useful elements in MBT resonates with theoretical tenets of (borderline) personality pathology, in particular attachment disturbances and emotional dysregulation. Patients highlights what we would label working in the therapeutic relationship, addressing transferential and counter-transferential processes explicitly, emotional validation, and enhancing mentalizing in its own right.